Feelings of indebtedness and guilt toward donor and immunosuppressive medication adherence among heart transplant (HTx) patients, as assessed in a cross‐sectional study with the Basel Assessment of Adherence to Immunosuppressive Medications Scale (BAASIS). Issue 10 (19th August 2017) - Shemesh, Yedida; Peles‐Bortz, Anat; Peled, Yael; HarZahav, Yedael; Lavee, Jacob; Freimark, Dov; Melnikov, Semyon
Abstract: Background: Nonadherence (NA) to immunosuppressive (IS) medications after organ transplant is a major risk factor for transplant failure, morbidity, and treatment costs. This study examined the association between feelings of indebtedness and guilt toward the donor, and IS medication adherence among HTx patients. Methods: In this cross‐sectional, descriptive, correlational study, a convenience sample of 102 HTx patients, from the outpatient facility of a tertiary medical center in Israel, completed the BAASIS, a validated instrument for assessing adherence, and reported their feelings of indebtedness and guilt toward the donor. Results: Missing a dose or skipping two or more doses, taking medication >2 hours before or after the recommended dosing time, altering the prescribed amount, or completely stopping the IS treatment in the last 4 weeks, characterized 64 patients (64%). The highest score received the item "timing nonadherence, " characterizing 58 patients (56.9%). Age, waiting time, and time since transplant, guilt feelings, and indebtedness to donor explained 17% (R 2 =.17) of the variance in adherence (χ 2 (5) =13.22, P =.021), with age, time since transplant, and guilt feelings significantly explaining adherence. Conclusion: Physicians and nurses should inquire about the presence of guilt feelings, as they might be associated with NA to medications after HTx.